568 Neonatal Hemolytic Uremic Syndrome. (October 2012) - Tiwari, L; Vashisht, N; Kaur, P; Gupta, N; Saikia, B; Puliyel, J
Abstract : Haemolytic uremic syndrome (HUS) is characterised by the triad of non immune haemolytic anaemia, thrombocytopenia and renal failure. It is rare in newborns. Only 5 cases of neonatal HUS have been reported to-date. We describe a series of 2 cases of neonatal HUS where one had definite history of birth asphyxia and another was an abandoned baby without clinical details about perinatal period. The known modalities of treatment include transfusion of plasma and plasmapheresis. In first baby haematological and renal parameters improved after double volume exchange transfusion while second baby responded to transfusion of fresh whole blood (packed red cells + plasma). Exchange transfusion essentially provides plasma exchange besides augmenting the haemoglobin levels. Arguably this is the first report of neonatal HUS treated with exchange transfusion.